The New Evangelicals: Expanding the Vision of the Common Good - Pally, Marcia (Grand Ripids, Mich. Wm. B. Eerdmans Publishing Company, 2011)
Marcia Pally reveals the "new evangelicals"--A growing movement that espouses antimilitaristic, anticonsumerist, and liberal democratic ideals and promotes poverty relief, immigration reform, and environmental stewardship. Combining analysis with numero
Keywords: Evangelicalism -- United States. Church and state -- United States. Liberalism -- Religious aspects -- Protestant churches